Proteome of bull fertility: a comparative study between resting and in-service Nellore bulls - Udoekong, Ekaette Chris (2023)
This study aimed to analyses sperm proteome of Nellore bulls by comparing their sperm protein profiles and identifying differentially abundant proteins during their in-service and resting periods. A total of twenty bulls aged between 19.8 and 22.7 months were investigated at their resting period and at the breeding season (in-service). Semen samples were collected from bulls by electroejaculatation and preserved in liquid nitrogen. A total of 155 sperm proteins were identified from the protein analysis using SDA-PAGE. 84 of these proteins were specific to both resting bulls and in-service bulls while 61 were found only in resting bulls and five found only in the samples from in-service bulls. The differentially expressed sperm proteins observed in sodium dodecyl sulfate polyacrylamide gel electrophoresis were identified using LC-MS/MS. In resting bulls, albumin was differentially expressed and significantly (p<0.05) lower, down regulated in in-service bulls. SRN, bovin proacrosine, GAPDHS, ASRGL1, BSP1, CES5A, SPACA3, SPAM1, ADAM32 and ACE were significantly (p<0.05) lower and down regulated in in-service bulls. SPADH1 and LOC101907989 were differentially expressed in in-service bulls, significantly (p<0.05) lower and down regulated in resting bulls; SPADH1 (spermadhesin-1) associates with seminal plasma proteins BSP-30k Da, seminal plasma PDC-109, seminal plasma A3, ANG1, RNASE4, SRN and carbohydrate-binding proteins (uncharacterized protein). These findings suggest that these sperm proteins play significant role and are associated with increased fertility in bull during in-service periods rather than when they are at rest. This study suggests prior clean-up of breeding bulls before breeding season to allow for biological processes and favorable correlations of other sperm protein like SPADH1 in the regulation of sperm maturation, functions, fertility and oocyte-sperm interaction. Keywords: Fertility. Seminal plasma proteins. Spermadhesin-1.